ANALISIS PENERAPAN AKUNTANSI BIAYA LINGKUNGAN TERHADAP LABA PERUSAHAAN PT. IMECO BATAM TUBULAR - Jaya, Hendry (MEASUREMENT : Jurnal Program Studi Akuntansi, 2015)
Implementation of environmental cost accounting is one form of concern for the environment of a company, because the environment contributes to the company. The purpose of this study was to determine and analyze the implementation of the environmental cost accounting of corporate profits as well as how companies disclose environmental costs in the financial statements.            This researchwas conducted at PT. ImecoBatam Tubular. This study is a descriptive qualitative research and in this study using secondary data. Based on the result of research at PT. ImecoBatam Tubular obtained that the company has not maximized in implementation of environmental cost accounting. Company in recognizing the environmental costs (waste management costs) included as costs of outside efforts by the consideration that the cost incurred as a service fee for management or waste disposal, and the costs will affect the company profits.Key word :      Environmental Accounting Cost Implementation, Environmental Accounting, Environmental Costs, Waste Management Cost, Company Profits.